2018
DOI: 10.1364/josaa.35.001760
|View full text |Cite
|
Sign up to set email alerts
|

Multiple invisibility regions induced by symmetry breaking in a trimer of subwavelength graphene-coated nanowires

Abstract: Electromagnetic response is studied for clusters of subwavelength graphene-coated nanowires illuminated by a linearly polarized plane wave in the terahertz frequency range. The solution of the scattering problem is obtained with the Lorenz-Mie theory and the multiple cylinder scattering formalism. The results show that normalized scattering cross-sections of nanowire clusters can be drastically changed by the symmetry breaking introduced into the cluster's design. This effect is due to excitation of dark modes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Recently, graphene has also been proposed as a coating material [18][19][20][21]. While this approach is very effective, its implementation at the nanoscale remains a complex task with the current technological resources.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, graphene has also been proposed as a coating material [18][19][20][21]. While this approach is very effective, its implementation at the nanoscale remains a complex task with the current technological resources.…”
Section: Introductionmentioning
confidence: 99%
“…The scattering efficiency and field distributions were shown in Figure 12c,d. Later, invisibility in a trimer of GCNWs was presented by Fesenko et al [128]. For TM-polarized incident waves, the normalized scattering cross-section spectra of all structures (GCNW, GCNW dimer, GCNM trimer) behaved similarly and exhibited a single invisible region.…”
Section: Optical Cloakingmentioning
confidence: 91%
“…This, for instance, was demonstrated in [21] where the THz wave scattering and absorption by a graphene strip grating embedded into a dielectric slab was analyzed with the aid of regularizing method-of-moments. Curved graphene-dielectric configurations studied so far have been mainly restricted to fully covered circular dielectric rods [22][23][24][25]. Arbitrary dielectric rod, fully covered with graphene, was analyzed with boundary integral equation in [26].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Our study has shown that the best fit of the first-order plasmon-mode resonance is provided by / 4    . Note that the expression (21) is more accurate than equation (25) of [10], which can be obtained by setting Z = 0.…”
Section: Graphene Conductivity and Plasmon Resonancesmentioning
confidence: 99%